A Tertiary Home Health Care Center: Reasons for Applications and Consultations (Annals of Medical Research, 2021)
Aim: As home health care centers develop in our country, expectations of patients and their relatives increase. This study was planned to show the most frequent reasons for application and the service given by a home health care center.